Guía de técnicas de impresión para la producción de calzado deportivo en Tungurahua - Rojas Muso, Andrea Pamela (2024)
The present project addresses the operational and market challenges faced by the sports footwear industry in Tungurahua due to the incorrect application of printing techniques. The lack of investment in technology and training, along with the absence of solid internal policies, contribute to the production of footwear of variable quality and the generation of waste. This results in the loss of customers, negative environmental impact, and competitive disadvantage. To address these issues, a printing techniques guide is proposed, which will provide parameters and guidelines to improve efficiency, reduce waste, and ensure the quality of the final product. This guide will offer footwear companies practical tools and updated knowledge, driving continuous improvement and strengthening their position in the market as leaders in sustainability and quality.